Endogenous protein and enzyme fragments induce immunoglobulin E‐independent activation of mast cells via a G protein‐coupled receptor, MRGPRX2. (2nd April 2018) - Tatemoto, K.; Nozaki, Y.; Tsuda, R.; Kaneko, S.; Tomura, K.; Furuno, M.; Ogasawara, H.; Edamura, K.; Takagi, H.; Iwamura, H.; Noguchi, M.; Naito, T.
Abstract: Mast cells play a central role in inflammatory and allergic reactions by releasing inflammatory mediators through 2 main pathways, immunoglobulin E‐dependent and E‐independent activation. In the latter pathway, mast cells are activated by a diverse range of basic molecules (collectively known as basic secretagogues) through Mas‐related G protein‐coupled receptors (MRGPRs). In addition to the known basic secretagogues, here, we discovered several endogenous protein and enzyme fragments (such as chaperonin‐10 fragment) that act as bioactive peptides and induce immunoglobulin E‐independent mast cell activation via MRGPRX2 (previously known as MrgX2), leading to the degranulation of mast cells. We discuss the possibility that MRGPRX2 responds various as‐yet‐unidentified endogenous ligands that have specific characteristics, and propose that MRGPRX2 plays an important role in regulating inflammatory responses to endogenous harmful stimuli, such as protein breakdown products released from damaged or dying cells.